Heavy metals in prawn feed, pond water, sludge, soil and prawn muscles - Marlini, Binti. Mohd Rizan. (Universiti Malaysia Sarawak (UNIMAS), 2006)
In this study, concentrations of Zo, Mn, Cu, Ph and Cd were determined in pond water, sludge, prawn tissue, feed and soil from 3 different ponds of TeJaga Air and Asajaya farms. Zn was found to have the highest concentration in almost of all samples analyzed. Heavy metal concentrations of Telaga Air pond sludge descended in the order Zn> Mn >Pb >Cu > Cd. Meanwhile, metal concentrations in Asajaya pond sludge are as followed Mn> Zn> Pb> eu> Cd. Statistically, significant differences in metal concentrations in sludge were observed between layers and distances (p< 0.005). Correlation analysis carried out shows no significant correlation between metal concentrations in prawn tissue with that in sludge and water hut significantly correlated with the prawn feeds (.-=0 0.613). This indicated that prawn has regulatory mechanism which resists the uptake of metals from the surrounding into their tissue. Concentration of Pb and Mn in pond water from both farms were exceeded the Malaysian water quality standard. Feed used for minerals supplement in Telaga Air farm comparatively higher concentration of Zn, Mn and Ph than the feed used in Asajaya farm.